2004
DOI: 10.2337/diabetes.53.11.3013
|View full text |Cite
|
Sign up to set email alerts
|

Association of Protein Tyrosine Phosphatase 1B Gene Polymorphisms With Measures of Glucose Homeostasis in Hispanic Americans

Abstract: P rotein phosphorylation at tyrosine is a key regulatory event that modulates intracellular signaling pathways involved in signal transduction. Protein tyrosine phosphatase (PTP)-1B is a ubiquitously expressed protein (1) that catalyzes the dephosphorylation of proteins at tyrosyl residues. PTP-1B has been implicated (2-4) in negatively regulating insulin signaling by dephosphorylating the phosphotyrosine residues of the insulin receptor kinase activation segment of the insulin receptor. In mouse models, disru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
59
6
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 20 publications
10
59
6
4
Order By: Relevance
“…The function of PTP1B and PTPN2 in these pathways has been a focus for type 2 diabetes (T2D) which is associated with the PTPN1 gene [79][80][81]. Although the PTPN2 gene is not associated with susceptibility to T2D, altered PTPN2 expression can impact hepatic gluconeogenesis.…”
Section: The Role Of Ptpn2 In the Development And Progression Of T1dmentioning
confidence: 99%
“…The function of PTP1B and PTPN2 in these pathways has been a focus for type 2 diabetes (T2D) which is associated with the PTPN1 gene [79][80][81]. Although the PTPN2 gene is not associated with susceptibility to T2D, altered PTPN2 expression can impact hepatic gluconeogenesis.…”
Section: The Role Of Ptpn2 In the Development And Progression Of T1dmentioning
confidence: 99%
“…In a study of white subjects, Bento et al observed associations between several non-coding singlenucleotide polymorphisms (SNPs) positioned across PTPN1 and type 2 diabetes [2], whereas, in a study of Hispanic American subjects, Palmer et al observed associations between several of the same SNPs and insulin sensitivity and/or fasting glucose levels [3]. Subsequent replication studies of these initial reports have provided weaker or negative results for associations with type 2 diabetes or related phenotypes [4][5][6].…”
Section: Introductionmentioning
confidence: 80%
“…None of the 26 polymorphic SNPs was associated with either type 2 diabetes or BMI (Table 1). Although the sample size of the 1,037 subjects is comparable or larger than the Bento et al [2] and Palmer et al [3] studies, it may nonetheless have low statistical power to detect variants with modest effects. The power to detect an association depends on the number of case and control subjects, the prevalence of disease and the effect of the associated alleles (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Common variants in peroxisome proliferator-activated receptor-␥ (13) and KCNJ11 (14) may predispose to type 2 diabetes with relatively low odds ratios (approximately 1.2). Variants that affect insulin signaling through IRS-1 (15,16) and glucose homeostasis PTPN1 (17,18) seem to be less common in frequency, suggesting that combinations of rare and common variants contribute to risk for type 2 diabetes in different pathways in different populations.…”
Section: Genetics Of Diabetesmentioning
confidence: 99%